PENGEMBANGAN KONSEP E-GOVERNMENT BERBASIS ICT UNTUK MASYARAKAT PINGGIRAN KOTA (STUDI KASUS : KOTA PALEMBANG) - Ahkmad Ipandy; Darius Antoni (Jurnal Ilmiah Matrik, 2023)
The development of e-government is being carried out continuously. However, the goal of equitable utilization of e-government development has not been as expected, especially for people who live in the suburbs. For this reason, it is necessary to conduct research on the development of the concept of e-government for people who live in the suburbs. This concept is seen from Information and Communication Technology (ICT) aspect in the suburban community. There are six variables in this study. Those are an internet connection, transaction center, telecenter, government services, ICT training and education facilities, and information media. This research used qualitative methods. It was conducted to obtain all the facts related to the development of an ICT-based e-government model for suburban communities in Palembang